Relationship between rickets and incomplete distal renal tubular acidosis in children - Oduwole Abiola O; Giwa Olayiwola S; Arogundade Rasheed A (BMC, 2010)
Abstract Background In the Sub Saharan Africa Rickets has now been established to be due primarily to calcium deficiency and sometimes in combination with vitamin D deficiency. The main thrust of management is calcium supplementation with or without vitamin D. An observation was made that some children with nutritional rickets do not respond to this management modality. The recently reported high prevalence of Incomplete Distal Renal Tubular Acidosis (idRTA) in adults with osteoporosis as brought to fore the possibility of this being a possible cause of calcium wastage and therefore the poor response in these group of children with rickets. Aim To determine the prevalence of idRTA amongst a cohort of subjects with rickets To show a relationship between rickets and incomplete distal renal acidosis To determine the response of children with rickets and idRTA to addition of Shohl's solution to therapy Methodology Two separate cohorts of children with rickets performed the ammonium chloride loading test to detect those with incomplete renal tubular acidosis. Following identification for idRTA, Shohl's solution was added to therapy of calcium and vitamin D supplementation and their response compared to those without idRTA on calcium and vitamin D supplementation solely. Results 50 children with rickets aged from two to six years of age and composed of 29 females and 21males were investigated. Incomplete renal tubular acidosis was found in 38% of them. Prevalence of idRTA was highest amongst those aged 3-6 years of age. Those with idRTA had worse limb deformities, biochemical and radiological parameters than those who hadn't. Rate of response on those with idRTA treated with Shohl's solution was at par with those without idRTA. Conclusion Incomplete idRTA exist amongst children with rickets and should be looked out for in severe rickets and older children. Treatment of idRTA will lead to optimal response and healing of rickets.